The Role of Taxes in Supporting Sustainability: An Integration of Economic and Environmental Perspectives - Sapiri, Muhtar (Manunggal Halim Jaya, 2025)
This qualitative literature review explores the intersection of taxation and sustainability, aiming to provide a comprehensive understanding of the role of taxes in promoting environmental stewardship and economic efficiency. The research methodology involves systematic search, selection, and thematic analysis of relevant scholarly articles, books, and reports. Key findings indicate that environmental taxation serves as a pivotal policy tool for internalizing externalities, incentivizing innovation, and driving behavioral change towards sustainable practices. Carbon taxes and eco-taxes on pollutants have demonstrated effectiveness in reducing emissions and pollution levels while generating revenues for environmental conservation. However, challenges persist in addressing distributional impacts and safeguarding industrial competitiveness. Behavioral insights suggest that framing tax policies in terms of social norms and incorporating behavioral nudges can enhance compliance and foster pro-environmental behavior. Institutional contexts play a critical role in shaping the effectiveness of environmental tax policies, highlighting the need for holistic policy frameworks that balance environmental objectives with economic considerations. Future research should focus on evaluating the long-term impacts of environmental taxation, exploring innovative tax instruments, and adopting interdisciplinary approaches to address sustainability challenges comprehensively.